Pengaruh Citra Merek (Brand Image) Terhadap Keputusan Pembelian Online Kosmetik Perawatan Wajah Skintific - Nabila, Nabila; Ayuningtyas, Nurina; Atmanto, Dwi (Academy of Education Journal, 2024)
Brand image is important for a product, with a good brand image, it can influence consumer preferences to make purchasing decisions. However, at this time, brand reputation is not the main factor for consumers when considering purchasing beauty products. This study aims to determine the effect of brand image on online purchasing decisions for Skintific facial care cosmetics. This research method uses a quantitative approach with a survey method. Data was collected through questionnaires distributed to 96 respondents with a sampling method in the form of nonprobability sampling with a purposive sampling technique. Based on the simple linear regression test, the significance value of the X and Y variables is 0.000 <0.05. In the T test, the significance value is 0.000 <0.05 and the t value is 10.328> t table 1.98552, so it can be concluded that Ha is accepted and Ho is rejected. In the determination coefficient test, the coefficient of determination is 0.532, which means that the influence of brand image contributes 53.2% to the online purchasing decision for Skintific facial care cosmetics, while the remaining 46.8% is influenced by other variables not examined in this study. The results showed that brand image has a positive and significant influence on online purchasing decisions for Skintific facial care cosmetics.